Cellular Cardiomyoplasty – Challenges of a New Era - Kankuri, Esko; Lampinen, Milla; Harjula, Ari (Current Tissue Engineering (Discontinued), 2015)
Cell therapy for the failing heart has advanced in distinct phases or era with a first transition from dynamic to cellular cardiomyoplasty. Currently, the quest is to find the optimal replacement cell type or to engineer a substitute for the dysfunctional scarred tissue. Cell therapies still require major refinements before they can—in a truly therapeutic manner—aid the suffering myocardium that fails either to adequately support contraction or to permit dilatation. Here, we outline the road so far and provide an insight into current and future challenges that await resolving.
Keywords: cardiomyoplasty